Report on Mortgage Lending Practices in Milwaukee County: Part Two - (:unkn) unknown (My University, 2007)
This analysis prepared for Legal Action of Wisconsin as part of its examination of housing issues facing low-income residents identifies refinancing loans, subprime lending and other mortgage practices affecting employed and retired families in Milwaukee County. The report examines 420,633 mortgage loans issued in Milwaukee County, including 49,180 loans issued by subprime lenders, for the period from 1993 through 2001 and 2003 through 2005, using the last available Home Mortgage Disclosure Act (HMDA) data files. Of particular concern are refinancing loans where home owners take out new mortgages to obtain cash for credit card and other debt obligations. Central city residents, whose full value housing assessments have reported increases of $25,000 to $60,000 or more in the last six years, have been targeted for refinancing loans. For lower-income residents refinanced mortgages offer new found cash and illusory relief for consolidating credit card and other debts, but put owners’ entire home equity in jeopardy if they cannot make their payments. The CDBG neighborhoods recorded over 5,000 refinancing loans a year to owner occupants from 2003 through 2005.
Keywords: foreclosures; predatory lending; subprime lending; morgages